2021
DOI: 10.1111/jam.15164
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of adaptive response to ferulic acid and p ‐coumaric acid after physiological stresses in Cronobacter sakazakii

Abstract: Aim: The present study demonstrated the antimicrobial activity of ferulic acid and p-coumaric acid against unstressed and stressed (cold stressed, starved and desiccated) Cronobacter sakazakii in laboratory media (37°C) and reconstituted powdered infant formulation (PIF) with mild heat treatment (50°C). Methods and results: Five phenolics, namely, quercetin, rutin, caffeic acid, ferulic acid and p-coumaric acid, were tested for antimicrobial activities against five strains of C. sakazakii either unstressed or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Plant antimicrobials were widely used for their safety, environment-friendly, no drug resistance, and low residue, among other advantages. Studies have revealed that some phenolic substances showed antibacterial activities, for example, they be inserted into the phospholipid layer of bacterial membranes, disrupting the van der Waals interaction between the fatty acyl chains and destroying the phospholipid bilayer and membrane integrity ( Burt, 2004 ; Chauhan et al, 2021 ; Li et al, 2021 ). As the ion gradient of the cell membrane is disrupted, important components such as ions and macromolecules are released from within the cell, resulting in the death of the bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Plant antimicrobials were widely used for their safety, environment-friendly, no drug resistance, and low residue, among other advantages. Studies have revealed that some phenolic substances showed antibacterial activities, for example, they be inserted into the phospholipid layer of bacterial membranes, disrupting the van der Waals interaction between the fatty acyl chains and destroying the phospholipid bilayer and membrane integrity ( Burt, 2004 ; Chauhan et al, 2021 ; Li et al, 2021 ). As the ion gradient of the cell membrane is disrupted, important components such as ions and macromolecules are released from within the cell, resulting in the death of the bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Natural plant extracts, such as essential oils and organic acids, have a specific antibacterial effect [ 1 ]. Essential oil exerts a bacteriostatic effect on multiple targets in bacteria by disrupting the bacterial membrane and reducing the intracellular ATP concentration and intracellular pH value [ 2 , 3 ]; thus, developing antibiotic resistance is not easy.…”
Section: Introductionmentioning
confidence: 99%